The strategies and barriers addressed by occupational therapists in the process of successful work-related transitions for clients who have sustained serious hand injuries - Uys, Michelle Elizabeth (Stellenbosch : Stellenbosch University, 2020)
Thesis (MOccTher)--Stellenbosch University, 2020.